Originalism and the Good Constitution - JOHN O. McGINNIS, MICHAEL B. RAPPAPORT (Harvard University Press, 2013)
Originalismâ€”the view that the Constitution should be interpreted according to its original meaningâ€”has been an important principle of constitutional interpretation since the early republic. James Madison, the father of the Constitution, wrote: â€œI entirely concur in the propriety of resorting to the sense in which the Constitution was accepted and ratified by the nation. In that sense alone it is the legitimate Constitution. And if that be not the guide in expounding it, there can be no security for a consistent and stable . . . exercise of its powers.â€1 Today this theory has prominent adherents on the Supreme Court in Justice Clarence Thomas and, at least in â€œfaint-heartedâ€ form, Justice Antonin Scalia. Heller v. District of Columbia recently featured both majority and dissenting opinions that were wholly originalist in style. Legal academics across the political spectrum espouse some version of originalism.2 Nevertheless, originalism continues to be plagued by challenges, the most salient being how it is to be justified. But originalism is also confronted by many other fundamental questions. What is the precise nature of an originalist method of interpretation? Isnâ€™t it wrong for the living to be governed by the dead hand of the past? How can an originalist jurisprudence address the hundreds of judicial decisions inconsistent with original meaning that are now deemed the law of the land? A more general sense of disquiet underlies these specific questions. Law in general, and constitutional law in particular, should be measured by its contribution to our current welfare. Originalism seems to be focused on the distant past rather than the present and, on its face, does not concern itself with desirable results. Thus, it seems vulnerable to the central claim of living constitutionalismâ€”that interpretation of the Constitution should be guided by a modern vision of a good society that likely differs substantially from that of the long-dead Founders.In this book, we present a new normative defense of constitutional originalism that connects this interpretive method directly to the concept of a good constitution. We argue that originalism advances the welfare of the present-day citizens of the United States because it promotes constitutional interpretations that are likely to have better consequences today than those of nonoriginalist theories. The benefits of ordinary legislation for society and the proper theory of its interpretation are routinely connected to the virtues of lawmaking by a democratic legislature. We likewise connect the benefits of a desirable constitution and the proper theory of constitutional interpretation to the virtues of the constitution-making process.